A80 ENDOSCOPIC HEALING WITH USTEKINUMAB IN CROHN'S DISEASE: THE UNITI ENDOSCOPY SUB-STUDY. (1st March 2018) - Feagan, B G; Sandborn, W; Gasink, C; Chan, D; Lang, Y; Pollack, P; Hanauer, S; Wolf, D; Jacobstein, D; Johanns, J; Szapary, P; Rutgeerts, P
Abstract: Aims: To evaluate endoscopic healing in the ustekinumab (UST) induction (UNITI-1&2) & maintenance (IM-UNITI) phase 3 studies. Methods: Substudy patients (pts) had colonoscopies at baseline (UNITI Wk0), then 8 & 52 weeks later (IM-UNITI Wk44). Video-endoscopies were centrally read by a single blinded reader for ulcerations & SES-CD. In UNITI, pts received one IV dose (UST 130mg, UST ~6mg/kg, or PBO). Pts with clinical response [CR] (CDAI drop≥100) in UNITI were re-randomized to subcutaneous (SC) PBO or UST 90mg (q12w or q8w) [primary randomized IM-UNITI population]. Non-randomized pts were added to the pooled IM-UNITI population: UST IV non-responders - SC UST 90mg, then SC UST 90mg q8w if in CR 8wks later; PBO IV non-responders - UST IV 130mg, then SC UST 90mg q12w if in CR 8wks later; PBO induction responders - PBO throughout. Pts required SES-CD ≥3 at UNITI Wk0 to be included. Primary outcome: Change in SES-CD at UNITI Wk8 (combined UST vs PBO). IM-UNITI Wk44 efficacy was evaluated for both the IM-UNITI populations. Results: At wk8, UST reduced SES-CD significantly more vs PBO. Results were similar across UST doses, studies, & other endpoints (Table 1a). At IM-UNITI Wk44, in the primary randomized IM-UNITI population trends favoured UST vs PBO maintenance (especially UST 90mg q8w) but small sample sizes (UST n=46; PBO n=24) limited conclusions. In the post-hoc pooled IM-UNITI population (Table 1b), trends supporting UST maintenance were favourable, especially 90mg q8w. Conclusions: The endoscopy substudy primary endpoint was met: One IV UST dose significantly reduced SES-CD vs PBO, as early as Wk8. More pts receiving UST maintenance achieved wk44 endpoints vs PBO. These data support efficacy of UST in inducing & maintaining endoscopic healing in CD. Funding Agencies: Janssen Research & Development, LLC